2009
DOI: 10.1016/j.cct.2008.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Why is recruitment to trials difficult? An investigation into recruitment difficulties in an RCT of supported employment in patients with severe mental illness

Abstract: BackgroundUnder-recruitment to randomised controlled trials (RCTs) is often problematic and there may be particular difficulties in recruiting patients with severe mental illness.AimTo evaluate reasons for under-recruitment in an RCT of patients with severe mental illnessMethodsQualitative study during the recruitment phase of an RCT of supported employment. Trial staff and recruiting clinicians were interviewed. Data were analyzed thematically using constant comparative techniques.ResultsRecruitment rates wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
120
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(126 citation statements)
references
References 29 publications
6
120
0
Order By: Relevance
“…Patients approached soon after admission discussed being focused on themselves at that time and that perhaps research participation would be viewed more positively when they felt more 'over the problem'. This suggests that recruiting patients at the beginning of an admission can be particularly challenging as has been found by others (Howard, de Salis, Tomlin, Thornicroft, & Donovan, 2009a).The way in which the study was initially described to patients also influenced their decision, and patients particularly appreciated researchers with good communication skills who were open about the research process and appeared very professional.…”
Section: Discussionmentioning
confidence: 92%
“…Patients approached soon after admission discussed being focused on themselves at that time and that perhaps research participation would be viewed more positively when they felt more 'over the problem'. This suggests that recruiting patients at the beginning of an admission can be particularly challenging as has been found by others (Howard, de Salis, Tomlin, Thornicroft, & Donovan, 2009a).The way in which the study was initially described to patients also influenced their decision, and patients particularly appreciated researchers with good communication skills who were open about the research process and appeared very professional.…”
Section: Discussionmentioning
confidence: 92%
“…The evaluation should incorporate site initiation and closeout as inexperienced sites and staff may require more assistance at these stages [23,31]. A major advantage of PRIME is that it can be undertaken by existing staff, which can enhance study cohesion and potentially reduce costs.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported a feeling among staff of needing to 'protect' patients, which can act as a barrier to recruitment. 10,11 In order to increase patient participation in research, it is important to ensure that clinicians feel confident and empowered to operate their brokerage roles effectively.…”
Section: Introductionmentioning
confidence: 99%